Environmental biotechnology : a biosystems approach - Vallero, Daniel A. (Amsterdam ; London : Academic Press, 2010)
"This single volume takes a biosystems approach to explore and explain the scientific and engineering principles and practices needed to understand the complexities of environmental biotechnology. Thoroughly covering physical, chemical and biological principles that support biotechnologies, Environmental Biotechnology's readable text and ample figures and tables provide a scientifically credible basis for an introduction to environmental biochemodynamics. Integrated with discussions of actual and potential risks of various biotechnologies on the environment, this book provides a context for researchers, practitioners, and students in previously disparate disciplines such as microbiology, systems biology, environmental engineering, risk assessment, ecology and genetic engineering to critically assess the efficacy and long-term effects of biotechnologies on the environment."--Jacket.
Ch. 1 Environmental biotechnology: an overview -- Ch. 2 A question of balance: using versus abusing biological systems -- Ch. 3 Environmental biochemodynamic processes -- Ch. 4 Systems -- Ch. 5 Environmental risks of biotechnologies -- Ch. 6 Reducing biotechnological risks -- Ch. 7 Applied microbial ecology: bioremediation -- Ch. 8 Biotechnological implications: a systems approach -- Ch. 9 Environmental risks of biotechnologies: economic sector perspectives -- Ch. 10 Addressing biotechnological pollutants -- Ch. 11 Analyzing the environmental implications of biotechnologies -- Ch. 12 Responsible management of biotechnologies -- App. 1 Background information on environmental impact statements -- App. 2 Cancer slope factors -- App. 3 Verification method for rapid polymerase chain reaction systems to detect biological agents -- App. 4 Summary of persistent and toxic organic compounds in North America, identified by the United Nations as highest priorities for regional actions -- App. 5 Sample retrieval from ECOTOX database for Rainbow Trout (Oncorhynchus mykiss) exposed to DDT and its metabolites in freshwater.
Includes bibliographical references and index.
Print version record.
Keywords: Bioremediation; Bioremediation -- Case studies; Bioremediation; Electronic books; Case studies